A study on noise emission in construction site / Nazrin A Rahman - A Rahman, Nazrin (2014)
Noise is defined as unwanted sound where this type of sound has been recognized by several organizations and parties as the potential hazard to the human. According to the World Health Organization (WHO) has categorize that the noise impact can be specific to noise issue such as hearing loss, interference with speech communication, disturbance of rest and sleep, psycho - physiological, performance effects, annoyance and effects on residential behavior live near to construction site. Nowdays, the noise issues likely to betaken severely in the development and planning of the housing project. This situation can be seen whereby there are many construction work was implemented near to residential area. During construction work in progress, has variety construction activities are carried out such as piling work, excavation work, concreting work and installation of formwork. From this construction activity, it will produce excessive noise and indirectly will impact to residents. By holding on this current issued, this research has been done whereby the aim of this research is to study the noise emission from nearby construction site to residential area. Then a comparison will be made of the noise level experience by the resident with the permissible noise level set up by the Department of Environment (DOE) with carry out noise measurement. Therefore, the end of this research based on data was gathered will come out with findings and the expected output will be one of the guideline as their reference in order to reduce the excessive of the noise level on construction sites.